The role of protein kinase C in diabetic microvascular complications - Pan, Deng; Xu, Lin; Guo, Ming (Frontiers in Endocrinology, 2022)
Protein kinase C (PKC) is a family of serine/threonine protein kinases, the activation of which plays an important role in the development of diabetic microvascular complications. The activation of PKC under high-glucose conditions stimulates redox reactions and leads to an accumulation of redox stress. As a result, various types of cells in the microvasculature are influenced, leading to changes in blood flow, microvascular permeability, extracellular matrix accumulation, basement thickening and angiogenesis. Structural and functional disorders further exacerbate diabetic microvascular complications. Here, we review the roles of PKC in the development of diabetic microvascular complications, presenting evidence from experiments and clinical trials.